Tradition and Power in the Roman Empire : Proceedings of the Fifteenth Workshop of The International Network Impact of Empire (Nijmegen, 18-20 May 2022) - Hekster, Olivier, (Classical Studies E-Books Online, Collection 2024., 2024)
This volume focuses on the interface between tradition and the shifting configuration of power structures in the Roman Empire. By examining various time periods and locales, its contributions show the Empire as a world filed with a wide variety of cultural, political, social, and religious traditions. These traditions were constantly played upon in the processes of negotiation and (re)definition that made the empire into a superstructure whose coherence was embedded in its diversity.